The Causative Factors Of Tidal Land’s Utilization in the Border Area Gajahmungkur Resevoir - Eppy Yuliani; Al’ Aswad; Izhati Qhoirina (International Conference on Coastal and Delta Areas, 2015)
One of the regional development manifestations in maximizing the field is a phenomenon of rise and subside field utilization in the border region of Gajahmungkur reservoir, Wuryantoro for citizen farming activity. The field which is being utilized is about 1.740.340 m2 or is about 174 acres. This utilization of the field is happening when the dam is subsided in the beginning of the dry season. There are many factors why the field in the border area is utilized. The aim of research is get to know the causative factors tidal land’s border area in Gajahmungkur reservoir, Wuryantoro, Wonogiri Regency is utilized. The research method that used in this research isrationalistic quantitative by collecting the data from the field survey and spreading questionnaire sheets. The analysis method which is used in this research is factor analysis and quantitative descriptive analysis. The result which is got from this research is the utilization of rise and subsided field in Wuryantoro was happening when the dam water is subsided in the dry season and was being utilized by the citizens for cultivation-farming activity. Several factors which become the cause of the rise and subsided field utilization are field-physical factor contains field measure, the price cost of rent and the field sale; government wisdom contains citizens understanding about the regulation of the rise and subsided field utilization and also the socialization of the field utilization toward the citizen; and economic factorcontains the gross level, citizen prosperity and the value of the field from the rise and subsided field, such as an easy access upon the location and the price of the ground sale. It has been being an expectation that there will be a good cooperation between Perum Jasa Tirta I and the citizen to keep the eternality and the function of Gajahmungkur reservoir.